2014
DOI: 10.1186/2040-2392-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomic analysis identifies sex-specific differences in lipid metabolism and inflammation profiles in adults diagnosed with Asperger syndrome

Abstract: BackgroundThe higher prevalence of Asperger Syndrome (AS) and other autism spectrum conditions in males has been known for many years. However, recent multiplex immunoassay profiling studies have shown that males and females with AS have distinct proteomic changes in serum.MethodsHere, we analysed sera from adults diagnosed with AS (males = 14, females = 16) and controls (males = 13, females = 16) not on medication at the time of sample collection, using a combination of multiplex immunoassay and shotgun label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…APOE is a significant factor in the neurodegenerative diseases. Here, it was found to be increased in the plasma of autistic patients, this is similar with a previous study . However, another previous study found no evidence for linkage or association of APOE to autism .…”
Section: Discussionsupporting
confidence: 92%
“…APOE is a significant factor in the neurodegenerative diseases. Here, it was found to be increased in the plasma of autistic patients, this is similar with a previous study . However, another previous study found no evidence for linkage or association of APOE to autism .…”
Section: Discussionsupporting
confidence: 92%
“…There is however, evidence for different protein blood biomarkers in males and females with ASD, specifically Asperger's syndrome. A recent MS study reported that females had differences in proteins related to lipid transport/metabolism versus controls, whiles males with Asperger's syndrome primarily had differences in inflammatory proteins [Steeb et al, ], confirming a prior study showing similar differences in adult males and females with Asperger's syndrome [Schwarz et al, ]. Our current results support that inflammatory biomarkers are present in males with ASD in the salivary proteome, but we do not yet know if the current protein signature generalizes to females.…”
Section: Discussionsupporting
confidence: 83%
“…There were moderate sample sizes in this study, but it will be important to replicate these findings, especially including female subjects, and investigate the source of the increased levels, which could be environmental or genetic in nature, and could be either maternally or fetally derived. Additionally, although fT levels do not appear to be related to postnatal testosterone levels in young children or adults, some hormone dysfunction appears to be present in both males and females with ASD, including higher rates of precocious puberty and an increased incidence of PCOS and dysmenorrhea [8,68,7783]. …”
Section: Sex Hormone Theory: Are Fetal Testosterone Levels Linked To mentioning
confidence: 99%